Musical Creation Wong Wodha | Tabuh Kreasi Wong Wodha - I Ketut Gede Aditya Wiradarma (GHURNITA: Jurnal Seni Karawitan, 2024)
The mind is God's most valuable gift because it is with the mind that humans are said to be cultured creatures, and it is also the mind that leads humans to achieve the title of being dignified, superior and wise. A wise human being is a human being who is virtuous in acting, making decisions, and advising others. These things are done by paying attention to the welfare of everyone involved, not being subjective, selfish, or taking sides. Wise humans are usually also able to see and recognize patterns in certain situations before making decisions or acting. Moving on from human life which must adhere to the principles of wisdom, the principles of dharma made my intuition to package it into a form of creative percussion musical composition using the medium of Gong Kebyar gamelan with the title Wong Wodha which means a human who has intelligence, wisdom in the nature of a dignified and superior human being. Wong Wodha is quoted from the Kawi language with two syllables, namely wong and wodha, Wong which means human while Wodha means wisesan and wicaksana/wise. The creative method used in Wong Wodha's percussion creations is the method of Alma M. Hawkins which has several stages, namely: exploration, improvisation and forming. The creation of Wong Wodha's percussion work is divided into 4 parts, with the total duration of the work being 11 minutes. It is hoped that the realization of Wong Wodha's creative percussion work will increase the creativity of young artists in Bali to create a work that has the value of beauty and specialness in his creative percussion work.